Muslim Women of the Fergana Valley : A 19th-Century Ethnography from Central Asia - Nalivkin, V. P. (Vladimir Petrovich), 1852-1918; Kamp, Marianne; Nalivkina, Mariia͡ Vladimirovna (Book collections on Project MUSE., 2016)
Muslim Women of the Fergana Valley is the first English translation of an important 19th-century Russian text describing everyday life in Uzbek communities. Vladimir and Maria Nalivkin were Russians who settled in a "Sart" village in 1878, in a territory newly conquered by the Russian Empire. During their six years in Nanay, Maria Nalivkina learned the local language, befriended her neighbors, and wrote observations about their lives from birth to death. Together, Maria and Vladimir published this account, which met with great acclaim from Russia's Imperial Geographic Society and among Orientalists internationally. While they recognized that Islam shaped social attitudes, the Nalivkins never relied on common stereotypes about the "plight" of Muslim women. The Fergana Valley women of their ethnographic portrait emerge as lively, hard-working, clever, and able to navigate the cultural challenges of early Russian colonialism. Rich with social and cultural detail of a sort not available in other kinds of historical sources, this work offers rare insight into life in rural Central Asia and serves as an instructive example of the genre of ethnographic writing that was emerging at the time. Annotations by the translators and an editor's introduction by Marianne Kamp help contemporary readers understand the Nalivkins' work in context.